Micromechanisms of creep in clay‐rich gouge from the Central Deforming Zone of the San Andreas Fault. Issue 2 (9th February 2015) - French, M. E.; Chester, F. M.; Chester, J. S.
Abstract: We report the strength and constitutive behavior of gouge sampled from the Central Deforming Zone (CDZ) of the San Andreas Fault. Layers of flaked CDZ gouge were sheared in the triaxial saw cut configuration using the stress relaxation technique to measure the gouge strength over 4 orders of magnitude in shear strain rate and at rates as low as 5 × 10 −10 s −1 and within an order of magnitude of in situ rates. Deformation conditions correspond to the in situ effective normal stress (100 MPa) and temperature (65 to 120°C) at the sampling depth of 2.7 km. Gouge was sheared dry and with brine pore fluid at 25 MPa pore pressure. Dry gouge is stronger and more rate strengthening than brine‐saturated gouge. Brine‐saturated CDZ gouge strengthens with increasing strain rate and decreasing temperature, and the dependencies of strength on strain rate and temperature increase at rates below ∼5 × 10 −9 s −1 . At strain rates greater than ∼5 × 10 −9 s −1, the rate dependence is consistent with previous studies on the CDZ gouge conducted at even higher rates. The increase in rate dependence below ∼5 × 10 −9 s −1 indicates a change in the rate‐controlling deformation mechanism. The magnitude of the friction rate dependence parameter, a, and the temperature sensitivity of a are consistent with crystal plasticity of the phyllosilicates. We hypothesize a micromechanical model for the CDZ gouge whereby a transition from fracture and delamination‐accommodated frictional flow to crystal plasticity‐accommodated frictional flow occurs with decreasing strain rate. Key Points: CDZ gouge was deformed at near in situ strain rates using stress relaxation A change in deformation mechanism occurs at low shear strain rates Rate and temperature effects constrain the microphysics of frictional flow